2021
DOI: 10.1038/s41592-020-01049-4
|View full text |Cite
|
Sign up to set email alerts
|

CryoDRGN: reconstruction of heterogeneous cryo-EM structures using neural networks

Abstract: Cryo-EM single-particle analysis has proven powerful in determining the structures of rigid macromolecules. However, many protein complexes are flexible and can change conformation and composition as a result of functionally-associated dynamics. Such dynamics are poorly captured by current analysis methods. Here, we present cryoDRGN, an algorithm that for the first time leverages the representation power of deep neural networks to efficiently reconstruct highly heterogeneous complexes and continuous trajectori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
466
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(531 citation statements)
references
References 53 publications
7
466
0
Order By: Relevance
“…Additionally, performing cryo-EM on the 1-NO state may enable visualization of the different conformations present in the sample. In particular, advances in EM data processing techniques, such as the algorithm cryoDRGN, could facilitate the identification of discrete states and continuous conformational changes in heterogeneous samples [ 73 ]. Given these kinds of current, rapid advances in SAXS and EM analyses, there can be no doubt that understanding sGC from a structural perspective is only just beginning.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, performing cryo-EM on the 1-NO state may enable visualization of the different conformations present in the sample. In particular, advances in EM data processing techniques, such as the algorithm cryoDRGN, could facilitate the identification of discrete states and continuous conformational changes in heterogeneous samples [ 73 ]. Given these kinds of current, rapid advances in SAXS and EM analyses, there can be no doubt that understanding sGC from a structural perspective is only just beginning.…”
Section: Discussionmentioning
confidence: 99%
“…This issue becomes more important when other specimens of increased complexity are considered. A method that addresses this issue by approximating the continuous 3D density function of a single particle is CryoDRGN (Zhong et al, 2021), a deep neural network-based algorithm. Recent machine-learning methods may improve the protein density of experimental cryo-EM maps, while the use of generative adversarial networks (GANs) trained on pairs of 3D atomic models and their noise-free cryo-EM maps is shown to generate a more realistic ground-truth 3D density map (Sanchez-Garcia et al, 2020a).…”
Section: Processing (Cryo-)em Images From Native Extracts With a Focus On Machine Learningmentioning
confidence: 99%
“…Principal component analysis of the Z values assigned to all particles revealed that the two opposite states along the first principal component of variability correspond to a state with ALC1 tightly bound to SHL2 and the H4 tail (same state described in Figure 2) and a state in which the ATPase domain is only loosely bound to the nucleosomal DNA. We used the graph traversal algorithm implemented in cryoDRGN (Zhong et al, 2021) with intermediate steps chosen to traverse the distribution along the first two principal components, which run approximately parallel to the two UMAP axes in this case (Figure 3A). Because cryo-EM data do not contain temporal information per se, this approach cannot inform on kinetics and temporal order.…”
Section: Analysis Of Heterogeneity In the Cryo-em Data Reveals Additional Functional States Of Alc1mentioning
confidence: 99%
“…Given the evidence that the set of 43 698 still contained significant continuous heterogeneity, we then analyzed it with cryoDRGN (Zhong et al, 2021). All models were trained for 50 epochs on a single GPU.…”
Section: Analysis Of Heterogeneity In the Cryo-em Datasetmentioning
confidence: 99%